The Influence of Intellectual Capital on Company Performance Moderated by Knowledge Assets (Empirical Study on 2014-2018 LQ45 Index) - Aprilia Whetyningtyas; Dianing Ratna Wijayani; Rama Ade Taruna (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
This study aims to examine the effect of intellectual capital on company performance moderated by knowledge assets.The population in this study are companies that are members of the Indonesia Stock Exchange LQ45 index for the 2014-2018 period.The sampling method used was purposive sampling method and obtained 40 research samples. Data analysis in this study with Partial Least Square using SmartPLS version 3.0.Based on the research results, it was found that intellectual capital had a positive effect on company performance, knowledge assets had a negative effect on company performance and knowledge assets strengthened the effect of intellectual capital on company performance